A Case Study in Tipping: An Economic Anomaly - Megan Nelson (Crossing Borders: A Multidisciplinary Journal of Undergraduate Scholarship, 2017)
When dining in a restaurant or having a drink at a bar, do you tip? If yes, what do you base the tip amount on? Is it who you are with? Do men tip more than women? Do you tip less when your actions are masked by a larger group? The answers to these questions are something that economists have struggled to explain. The most difficult question being: Why do people pay an additional amount when they have absolutely no legal obligation to do so? This case study explores the variables that lead to higher or lower tip amounts in the service industry. Past research lacks actual data from real-time collection outside of the scrupulous eyes of a lab technician or survey administrator. It is this detail which sets the research outlined in this paper apart from the rest. The case study in tipping provided 3 dominate variables that effect tip amount, the economic concept of free-riding—which is defined as a person who chooses to receive the benefits of a public good or service or a positive externality without contributing to paying the cost of producing those benefits, gender differences and generational differences.